The energy-absorbing characteristics of two-dimensional periodic self-reinforced polypropylene (SRPP) sandwich panel - Ma, Quanjin; M. R. M., Rejab (Elsevier, 2023)
This paper is used the slotting technique to manufacture the self-reinforced polypropylene (SRPP) sandwich structure. The crashworthiness characteristics of the sandwich structures were measured as a function of relative density. In this research, particular focus is placed on examining the energy-absorbing characteristics of sandwich structures with honeycomb and star cores. It was concluded that the SRPP sandwich panel of star core with a length of 60 mm provided the best energy-absorbing characteristics. Moreover, it was shown that the height of the core structure of 30 mm was more stable than the core structure of 60 mm height. In addition, it was indicated that the failure behaviour was highly sensitive to the relative density of the core structure. Furthermore, the SRPP sandwich structure could potentially be used as an alternative lightweight material for recyclable structures.